Geographical Origin of Post-Landmine Injury Malaria Infections. (8th October 2014) - Durham, Jo; Battle, Katherine; Rickart, Keith; Shanks, G. Dennis
Abstract Objective In Cambodia, a highly landmine-contaminated country with endemic malaria, symptomatic falciparum malaria has been observed in patients presenting with traumatic landmine injuries. Because a link between recrudescence of symptomatic Plasmodium falciparum malaria and severe trauma is well established, we explored whether a link could be demonstrated between the geolocation of landmine amputations and malaria cases. Method Landmine amputation data in Cambodia (2005–2008) were compared with predicted measures of malaria endemicity. Data of injuries that had resulted in amputation were plotted over a surface of P falciparum parasite rates. Results No statistically significant correlation was found, possibly because the P falciparum endemicity surface was drawn from a model-based geostatistical prediction of infection prevalence and did not distinguish cases of recrudescence. The implication of this finding is that where symptomatic falciparum malaria has been observed in patients with landmine injuries, the cases were likely to be reactivated falciparum infections and not new cases. Conclusions Further research is needed to understand the relationship between P falciparum and trauma. To distinguish P falciparum recrudescence from new cases, a prospective registry is needed. Also, practitioners need to be aware of the possibility of post-injury malaria recrudescence in complex emergencies. (Disaster Med Public Health Preparedness. 2014;0:1-5)